TRANSFORMASI PENDIDIKAN AGAMA ISLAM DALAM PRESPEKTIF DEMOKRASI DAN MULTIKULTURALISME DI ERA DIGITAL - Merliana, Miranti; Shobahiya, Mahasri; Asy’arie, Musa (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The transformation of Islamic Religious Education (PAI) has become an urgent necessity in responding to the dynamics of democracy, cultural diversity, and the challenges of the digital era, which generate new moral issues such as intolerance, hate speech, and weak ethical conduct in the use of technology. This study aims to analyze an integrative model for transforming PAI through the perspectives of democracy, multiculturalism, and digital literacy grounded in Islamic values. The research employs a qualitative approach with an in-depth literature review of classical and contemporary Islamic educational theories, concepts of democracy and multiculturalism, digital ethics literature, and the thought of Shaykh Hamza Yusuf regarding adab and modern morality. The findings indicate that integrating democratic values into PAI strengthens dialogical and participatory cultures, while Islam-based multicultural education cultivates tolerance and empathy amid diversity. Furthermore, digital literacy and digital ethics must be positioned as core components of learning to address the moral challenges of the technological era. This study proposes a four-dimensional model for the transformation of PAI spirituality, democracy, multiculturalism, and digital ethics relevant to contemporary curriculum development and educational practice. In conclusion, an integratively transformed PAI is capable of shaping learners who are morally upright, digitally literate, tolerant, and civil. ABSTRAK Transformasi Pendidikan Agama Islam (PAI) menjadi kebutuhan mendesak dalam merespons dinamika demokrasi, keberagaman budaya, dan tantangan era digital yang melahirkan persoalan moral baru seperti intoleransi, ujaran kebencian, serta lemahnya etika penggunaan teknologi. Penelitian ini bertujuan menganalisis model transformasi PAI yang integratif melalui perspektif demokrasi, multikulturalisme, dan literasi digital berbasis nilai-nilai Islam. Metode penelitian menggunakan pendekatan kualitatif dengan studi pustaka mendalam terhadap teori pendidikan Islam klasik dan kontemporer, konsep demokrasi dan multikulturalisme, literatur etika digital, serta pemikiran Syekh Hamza Yusuf mengenai adab dan akhlak modern. Hasil penelitian menunjukkan bahwa integrasi nilai demokrasi dalam PAI memperkuat budaya dialogis dan partisipatif, sementara pendidikan multikultural berbasis Islam menumbuhkan toleransi dan empati dalam keberagaman. Selain itu, literasi digital dan akhlak digital perlu dijadikan komponen utama pembelajaran untuk menghadapi tantangan moral era teknologi. Penelitian ini menghasilkan model transformasi PAI empat dimensi spiritualitas, demokrasi, multikulturalisme, dan etika digital yang relevan bagi pengembangan kurikulum dan praktik pembelajaran masa kini. Kesimpulannya, PAI yang ditransformasikan secara integratif mampu membentuk peserta didik yang berakhlak mulia, cerdas digital, toleran, dan berkeadaban.